2014
DOI: 10.1080/14780887.2014.933919
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Client Laughter as Therapeutic Actions in Practice

Abstract: The widely presumed links between laughter and humour have raised questions about their roles in psychotherapeutic interactions. This study uses conversation analysis to explore client-initiated laughter and different kinds of responses to it. By examining sequences leading up to and following client laughter, we show two distinctive therapeutic actions that are accomplished. When particular lines of therapeutic questioning are being pursued, silence following client laughter functions to prompt further client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The present study adds to research already carried out in this field: Pomeroy and Weatherall (2014) explored client-initiated laughter and various different kinds of therapist response. They found that therapists accomplished two distinctive therapeutic actions: (a) silence following the client’s laughter in order to prompt additional talk, and (b) displaying that they also find the same thing amusing in order to build up a rapport with the client.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The present study adds to research already carried out in this field: Pomeroy and Weatherall (2014) explored client-initiated laughter and various different kinds of therapist response. They found that therapists accomplished two distinctive therapeutic actions: (a) silence following the client’s laughter in order to prompt additional talk, and (b) displaying that they also find the same thing amusing in order to build up a rapport with the client.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the client laughs to express her disagreement with the therapist, who does the right thing by then asking for more information concerning the cause of the misunderstanding. Remaining silent after the patient has laughed has the function of prompting her to continue speaking (Pomeroy and Weatherall, 2014). Once she has finished, the therapist’s request for further information may be interpreted as a desire to not interrupt the flow of the patient’s discourse and to maintain the focus on her disorder.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy and the use of external indexes mitigates the disagreement displayed by the client in line 8 and probably softens the emotional value of the theme treated. On the one hand, the therapist's silence after the client has laughed signals disalignment with the client's attempt to be humorous since the preferred response to laughter is generally laughter (Jefferson 1979), but on the other hand, given the therapeutic setting, it also has the function of prompting the client to continue speaking (Pomeroy & Weatherall 2014), which in fact he does (lines 12-13). Given that, in this case, the client is making fun of himself with regard to a personal problem, the main function of this attempt at humour is to attenuate the gravity of the issue, thereby reducing stress.…”
Section: Excerpt 2 1 Cmentioning
confidence: 99%
“…From an Aristotelian point of view, there are no tools in discourse analysis that allow us to understand the pleasure and pain of engaging in discourse or having a conversation with someone or the enjoyment of writing. Even laughter is interpreted as fulfilling interactional functions such as oppression (e.g., Walkerdine, 1981, on laughter) or building rapport (e.g., Pomeroy & Weatherall, 2014). Of course laughter may well achieve these functions but the place of laughter as a goal in itself within conversation is left out of the analysis.…”
Section: How To Categorise Discursive Materials In Social Psychology?mentioning
confidence: 99%